2010
DOI: 10.1177/0149206310383986
|View full text |Cite|
|
Sign up to set email alerts
|

The Cognitive Perspective in Strategy: An Integrative Review

Abstract: This article integrates the literature on strategic cognition (SC) within a framework that links the antecedents, structure, and process of SC with outcomes. Reviewing the literature from 1993 (two years prior to Walsh’s review of managerial and organizational cognition) until 2007, this article identifies three elements of SC structure (organizational identity, strategy frames, and organizational routines) and four SC processes (strategy formulation, strategy implementation, strategic change, and organization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
288
0
7

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 271 publications
(301 citation statements)
references
References 272 publications
(392 reference statements)
6
288
0
7
Order By: Relevance
“…Consistent with previous literature (e.g., Thomas, Clark, & Gioia, 1993; also see Narayanan et al, 2011, for a review of a related topic, strategic cognition), recent studies in this area find that cognitive influences on CEOs, whether examined in terms of their perceptions, attention, amount of information processed, or metacognitive experience, significantly influence a variety of firm outcomes including firm performance, flexibility, corporate entrepreneurship, and decision making (e.g., Kaplan, 2008;Mitchell et al, 2011). These studies examine firms in a variety of industries and use multiple techniques such as surveys, archival data, and field experiments, increasing our confidence in the validity and generalizability of the results.…”
Section: Cognitive Influences On Ceossupporting
confidence: 92%
“…Consistent with previous literature (e.g., Thomas, Clark, & Gioia, 1993; also see Narayanan et al, 2011, for a review of a related topic, strategic cognition), recent studies in this area find that cognitive influences on CEOs, whether examined in terms of their perceptions, attention, amount of information processed, or metacognitive experience, significantly influence a variety of firm outcomes including firm performance, flexibility, corporate entrepreneurship, and decision making (e.g., Kaplan, 2008;Mitchell et al, 2011). These studies examine firms in a variety of industries and use multiple techniques such as surveys, archival data, and field experiments, increasing our confidence in the validity and generalizability of the results.…”
Section: Cognitive Influences On Ceossupporting
confidence: 92%
“…Second, there is uncertainty about a partner's behavior once an alliance has been formed. Executives will infer such behavior from a competitor's reputation in the industry, which is also part of the organizational frame (Narayanan et al, 2011). Third, prior studies on corporate entrepreneurship have shown the importance of organizational frames for strategic decision-making.…”
Section: Contextmentioning
confidence: 99%
“…This includes points of view about industry cause-and-effect relationships, the nature of competition, and the status of competitors (Corner et al, 1994;Gilbert, 2006;Narayanan, Zane, & Kemmerer, 2011).…”
Section: Contextmentioning
confidence: 99%
“…The 'strategy-as-practice' perspective presented in Chia & Mackay, (2007) offers theoretical insights. Hodgkinson & Clarke (2007) proffer a model to aid the profiling of the cognitive characteristics of strategists, and Narayanan et al (2011) have reviewed the associated concept of 'strategic cognition'.…”
Section: Introductionmentioning
confidence: 99%